GAMBARAN PELAKSANAAN KEGIATAN KIA DI KABUPATEN SERANG - Witcahyo, Eri; Ma’rufi, Isa (IKESMA, 2013)
Serang is ones of district of Banten Province which has problem at maternal, neonatal, child health. Maternal and child mortality rate shows increase trend each years. The purpose of this study was to describe Maternal & Child Health activities implementation at communities. Type of research is descriptive by interview technique. Informants on the study are midwife coordinator and manager line at each Community Health Center (Sub District Pamarayan, Kramat Watu and Tirtayasa). The results showed that according to the informant are partnership between midwives and TBA has to improve, reward system is also give to community to increase their participate at all of Maternal & Child Health activities which held by government. Social activities at community are also the meaning part to improve Maternal & Child Health activities. According to the result, it is suggested to create innovative program for communities. It needs to use effective methods and media so that communities impress to join the activity. Participatory approach is also important to improve community participative.